Assessment of Postoperative Obturation Quality of Retreatment Cases - A Retrospective Study - Jerry Jose1 , Subash Sharma2 , Surendar Sugumaran (Institute of Medico-legal Publications Pvt Ltd, 2020)
Conventional endodontic therapy emphasizes many factors which mainly emphasize root canal disinfection.However there is a probability of endodontic therapy to give an unfavourable outcome such as persistentclinical symptoms and unfavourable periapical healing. The frequency of failure is reported to be around 20%and various factors contribute to it which mostly relies on the treatment procedure followed by the previousoperator. It is of paramount importance that postgraduate doctors should learn to treat these case scenarioswith high effectiveness. This study aims to assess the postoperative obturation quality of retreatment casesdone by graduate doctors. The study was done by using data collected from electronic medical records ofSaveetha Dental College, Chennai, India. The time frame of data collection was seen from June 2019 toMarch 2020. A total sample size of 230 was assessed radiographically and the quality of obturation wasanalyzed using 2 grading criteria in compliance with 2 operators. From the cases assessed, about 80% hadachieved correct radiographic length of obturation and about 70% of obturation was not of optimal quality.Quality of obturation was not adequate. The length of root canal filling was desirable whereas the quality ofcondensation was not adequate about 60% of the assessed cases